Tidlig neoliberalisme - Schulz-forberg, Hagen (Slagmark - Tidsskrift for idéhistorie, 2020)
This article maps the early conceptual and institutional history of neoliberalism, arguing that the social question was of vital importance to the ideology’s early de- velopment in the 1930s. This has been overlooked in recent intellectual histories of neoliberalism, which focus primarily on the post-war period. Those who have ventured into the prehistory of neoliberalism have primarily focused on the neoliberal acceptance of stronger state intervention in the economy, but without contextualizing this shift against the background of the social question. In addition, the article explores another overlooked dimension of early neoliberalism, namely the transnational institutional efforts that were indispensable to the foundation of the neoliberal network.